A lithofacies approach for modeling non‐Fickian solute transport in a heterogeneous alluvial aquifer. Issue 1 (29th January 2016) - Bianchi, Marco; Zheng, Chunmiao
Abstract: Stochastic realizations of lithofacies assemblage based on lithological data from a relatively small number of boreholes were used to simulate solute transport at the well‐known Macrodispersion Experiment (MADE) site in Mississippi (USA). With sharp vertical contrasts and lateral connectivity explicitly accounted for in the corresponding hydraulic conductivity fields, experimental results from a large‐scale tracer experiment were adequately reproduced with a relatively simple model based on advection and local dispersion. The geologically based model of physical heterogeneity shows that one well‐interconnected lithofacies, with a significantly higher hydraulic conductivity and accounting for 12% of the total aquifer volume, may be responsible for the observed non‐Fickian transport behavior indicated by the asymmetric shape of the plumes and by variations of the dispersion rate in both space and time. This analysis provides a lithological basis to the hypothesis that transport at MADE site is controlled by a network of high‐conductivity sediments embedded in a less permeable matrix. It also explains the calibrated value of the ratio of mobile to total porosities used in previous modeling studies based on the dual‐domain mass transfer approach. The results of this study underscore the importance of geologically plausible conceptualizations of the subsurface for making accurate predictions of the fate and transport of contaminants in highly heterogeneous aquifers. These conceptualizations may be developed through integration of raw geological data with expert knowledge, interpretation, and appropriate geostatistical methods. Key Points: Lithofacies are mapped as basis for 3‐D hydraulic conductivity distribution Non‐Fickian transport behavior emerges naturally from lithofacies distribution Verifiable explanations are developed for the plume behavior at the MADE site